Balconies: the linguistic landscape from the perspective of enaction (Signifiances (Signifying), 2024)
The aim of this paper is to reflect on the balcony in the linguistic landscape from the perspective of enaction. Initially, we delved into a vast interdisciplinary bibliography and gathered samples of the actual reality. Subsequently, we categorized, analyzed, and interpreted all the gathered information. Regarding its structure, this article begins with a methodological introduction. The main functions of the balcony –environmental, aesthetic, and, above all, communicative– are then explained. This is followed by a consideration of the specular and modelative aspects of this architectural element. The work concludes with an enactivist approach to the language of the balcony, in other words, by demonstrating that reality has an impact on the language of balconies, that this language affects reality, and that there is an interaction between the two.